2010
DOI: 10.1124/mol.110.063750
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Checkpoint Kinase 2 by 3,3′-Diindolylmethane Is Required for Causing G2/M Cell Cycle Arrest in Human Ovarian Cancer Cells

Abstract: We evaluated the effect of 3,3Ј-diindolylmethane (DIM) in ovarian cancer cells. DIM treatment inhibited the growth of SKOV-3, TOV-21G, and OVCAR-3 ovarian cancer cells in both a doseand time-dependent manner with effective concentrations ranging from 40 to 100 M. Growth-inhibitory effects of DIM were mediated by cell cycle arrest in G 2 /M phase in all the three cell lines. G 2 /M arrest was associated with DNA damage as indicated by phosphorylation of H 2 A.X at Ser139 and activation of checkpoint kinase 2 (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 43 publications
(46 reference statements)
4
48
0
Order By: Relevance
“…We have demonstrated previously that DIM inhibits the proliferation of ovarian cancer cells by inducing apoptosis (Kandala and Srivastava, 2010). We hypothesized that the growth suppressive effect of DIM in ovarian cancer cells was mediated by inhibiting EGFR activation.…”
Section: Dim Targets Egfr Signaling To Suppress Ovarian Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…We have demonstrated previously that DIM inhibits the proliferation of ovarian cancer cells by inducing apoptosis (Kandala and Srivastava, 2010). We hypothesized that the growth suppressive effect of DIM in ovarian cancer cells was mediated by inhibiting EGFR activation.…”
Section: Dim Targets Egfr Signaling To Suppress Ovarian Cancermentioning
confidence: 99%
“…It also is currently in clinical trials for prostate cancer (Heath et al, 2010). In our previous study, we showed that DIM exhibits antiproliferative properties in ovarian cancer cells by causing G 2 /M cell cycle arrest (Kandala and Srivastava, 2010). In the present study, we investigated the mechanism by which DIM inhibits the proliferation of ovarian cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations